Penerapan Metode Bermain Peran Dapat Meningkatkan Kemandirian Anak di RA Raudatul Ulum Bondowoso - Shovi Yatul Istifadah; Hosaini Hosaini; Andi Wapa (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
This research starts from the problems that exist in the independence of group A children, more precisely at RA Raudatul Ulum based on the results of observations made by researchers. The aim is to increase children's independent attitudes. This research uses the classroom action method with three cycles. As for the results of this research, it can be seen that in cycle I, of the 5 aspects assessed there was an increase to an average of 60% (poor category). There was an increase of 9% from cycle I. Meanwhile, after Cycle I was held there was a significant increase to 76% (good category) or an increase of 16% from cycle I. This shows that there was an increase of 25% from cycle I, meaning the teaching method Role playing can increase the level of independence in Group A RA Raudatul Ulum Bondowoso.